Estudo sobre o uso de cinza proveniente de termoelétricas na produção de argamassa de revestimento - Leite, Kelma Pinheiro (2012)
The power plants, with motive power from burning coal, have a high amount of ash residue from combustion. These can be used in construction to replace the traditional binders. The spread of non-renewable reuse of waste cited in the companies of the construction it is with full market growth conditions, hence the importance of research to spread their adoption. The present work aims to conduct research of technical feasibility for the use of ash in the execution of mortar coating. The relevance of this study is due to the necessity of reducing the negative environmental impacts and at the same time developing new technologies for construction, while reducing costs. By laboratory tests, compared to a mortar coating trace conventional (1:5) and mortars with different percentages of ash (10%, 20%, 30% and 40%), replacing the cement usually used. Tests of consistency index, compressive strength, tensile strength in bending, adhesion and water retention. The results indicate that there is sustainability in the use of gray with the replacement percentage of 20% for the 1:5 mark